Environmental DNA metabarcoding for benthic monitoring: A review of sediment sampling and DNA extraction methods - Pawlowski, J; Bruce, K; Panksep, K; Aguirre, F I; Amalfitano, S; Apothéloz-Perret-Gentil, L; Baussant, T; Bouchez, A; Carugati, L; Cermakova, K; Cordier, T; Corinaldesi, C; et al. (The Science of the total environment, 2022)
Environmental DNA (eDNA) metabarcoding (parallel sequencing of DNA/RNA for identification of whole communities within a targeted group) is revolutionizing the field of aquatic biomonitoring. To date, most metabarcoding studies aiming to assess the ecological status of aquatic ecosystems have focused on water eDNA and macroinvertebrate bulk samples. However, the eDNA metabarcoding has also been applied to soft sediment samples, mainly for assessing microbial or meiofaunal biota. Compared to classical methodologies based on manual sorting and morphological identification of benthic taxa, eDNA metabarcoding offers potentially important advantages for assessing the environmental quality of sediments. The methods and protocols utilized for sediment eDNA metabarcoding can vary considerably among studies, and standardization efforts are needed to improve their robustness, comparability and use within regulatory frameworks. Here, we review the available information on eDNA metabarcoding applied to sediment samples, with a focus on sampling, preservation, and DNA extraction steps. We discuss challenges specific to sediment eDNA analysis, including the variety of different sources and states of eDNA and its persistence in the sediment. This paper aims to identify good-practice strategies and facilitate method harmonization for routine use of sediment eDNA in future benthic monitoring.
Keywords: ekosystém; environmentální DNA; taxonomické DNA čárové kódování; Ecosystem; biodiverzita; DNA; Biodiversity; DNA Barcoding, Taxonomic; Aquatic ecosystems; Sediments; Monitoring; Environmental DNA; DNA, Environmental; Metabarcoding; Environmental Monitoring; monitorování životního prostředí